An Efficient Model for S.M.S Security and SPAM Detection: A Review - Zalpuri, Nikhila; Arora, Meena (International Journal of Computer Sciences and Engineering, 2025)
Short message service (S.M.S) security is a very important issue in today’s time. In spite of the fact that instant messengers have become very popular, S.M.S is still used. S.M.S is prone to several attacks and is not yet marked as a safe means for communication. Security in S.M.S includes message authentication, user authentication, encryption and decryption of the message and Spam .This paper deals with the survey of all these aspects of security in order find the best options available for each of them today .It is found that the most widespread functions are SHA-1(Secure Hash Algorithm- 1) and MD5(Message Digest) , MD5 hash algorithm when used with RSA provides a very strong means for authentication of the user , ElGamal algorithm is the most effective for encryption/decryption of SMS and SVM(Support Vector Machine) is the best machine learning technique for SPAM detection.